Pediatric Heart Failure in the Developing World - Ramakrishnan, Sivasubramanian (Reviews on Recent Clinical Trials, 2014)
The exact prevalence of heart failure among children of developing countries is not known, as the data is limited. The relative frequency of different causes of pediatric heart failure varies widely across different countries and even among different parts of large countries like India. Children of developing countries face a double burden of etiologies. Conditions such us congenital heart disease, myocarditis and cardiomyopathies are common causes of pediatric of heart failure. In addition, diseases like rheumatic heart disease, nutritional deficiencies, and other tropical diseases also result in heart failure among children of the developing countries. However, most of the developing countries have low resources and hence management of pediatric heart failure becomes challenging. Advanced therapies for heart failure are rarely used in children of developing countries and cardiac transplant remains a distant dream.
Keywords: tropical cardiomyopathy